2009
DOI: 10.1111/j.1528-1167.2009.02259.x
|View full text |Cite
|
Sign up to set email alerts
|

Histologic and morphologic effects of valproic acid and oxcarbazepine on rat uterine and ovarian cells

Abstract: SUMMARYPurpose: To determine the histologic and morphologic effects of valproic acid (VPA) and oxcarbazepine (OXC) on rat uterine and ovarian cells. Methods: Fifty-six female prepubertal Wistar rats (21-24 days old and weighing between 47.5 and 58.1 g) were divided equally into four groups, which were given drinking water (controls), 300 mg/kg/day of VPA, 100 mg/kg/day of OXC or VPA + OXC via gavage, for 90 days. Ovaries and uteri of rats on proestrous and diestrous phases of estrous cycle were extirpated and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
1
3

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 21 publications
0
5
1
3
Order By: Relevance
“…To the best of our knowledge, the literature contains no studies on the histopathological change in the testis tissue caused by OXC. This study demonstrates that in contrast to the negative effects in female rat ovarian tissues caused by OXC, 25,26 it does not lead to prominent changes in spermatogenetic cells and stages in male rats.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…To the best of our knowledge, the literature contains no studies on the histopathological change in the testis tissue caused by OXC. This study demonstrates that in contrast to the negative effects in female rat ovarian tissues caused by OXC, 25,26 it does not lead to prominent changes in spermatogenetic cells and stages in male rats.…”
Section: Discussionmentioning
confidence: 58%
“…Three more recent studies have reported that OXC causes edema and apoptosis in retinal ganglion cells, and ovarian and endometrial tissues. 25,26,31 OXC gives rise to swelling and edema in some cells, leading to impairment and subsequent apoptosis and cell death in cell organelles. This particularly occurs in more aged cells.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported that it had an apoptotic and degenerative effects on rat uterine and ovarian cells (Cansu et al, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Di Renzo et al () showed a relationship between axial skeletal malformations and increased apoptosis in somites caused by VA exposure in CD‐1 mice. VA has also been shown to cause apoptosis of uterine and ovarian cells in rats (Cansu et al., ). In embryo culture, VA caused oxidative stress and led to increased cell death (Tung and Winn, ).…”
Section: Discussionmentioning
confidence: 99%